Optical Coherence Tomography Angiography Analysis of Retinal and Choroidal Vascular Networks during Acute, Relapsing, and Quiescent Stages of Macular Toxoplasma Retinochoroiditis. - Azar, Georges; Favard, Catherine; Salah, Sawsen; Brézin, Antoine; Vasseur, Vivien; Mauget-Faÿsse, Martine (BioMed Research International, 2020)
Purpose. To highlight the advantages of optical coherence tomography angiography (OCTA) in delineating the morphological features of the retinal and choroidal vascular network during acute, relapsing, and quiescent stages of macular toxoplasma retinochoroiditis. Methods. This prospective study included patients presenting with both active and quiescent ocular toxoplasmoses. OCTA was obtained to diagnose and follow the subsequent vascular network changes at diagnosis and six months after acute presentation. Results. Twenty-three eyes of 23 patients were included. In active lesions, OCTA showed extensive, well-delineated areas of intense hyposignal and perifoveal capillary arcade disruption in the parafoveal superficial capillary plexus (pSCP) and less extensive hyposignal in the parafoveal deep capillary plexus (pDCP). Signals of decreased deep capillary density and disorganization were also seen in the choroid. In nonactive lesions, OCTA demonstrated a homogenous and equally attenuated grayish hyposignal of the pSCP and pDCP and a partial restoration of the nonperfused choroidal areas. Conclusion. OCTA is a useful technique for vascular network analysis in toxoplasma retinochoroiditis. It allows the visualization of the different network changes and behaviors during the different stages of the infection.